PEMBERDAYAAN UMKM SAMILER MELALUI DIGITALISASI PEMASARAN PRODUK DI ERA MEDIA SOSIAL - Ulum, M Bustanul; Hakim, Faisol; Fawaid, Ahmad (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service program aims to enhance the marketing capacity and visibility of samiler (cassava-based snacks) produced by MSMEs in Bintoro through an integrated digital promotion strategy that combines online channels with on-site visual markers. The program adopts an Empowerment-Based Research (EBR) approach using the ECA–EVAREDcycle (Exploration, Create & Action, Evaluation, Report & Dissemination). During exploration, the team mapped promotional needs, production–sales flows, and digital literacy barriers. The create & action stage comprised: (1) establishing an online storefront and product catalogue on Shopee; (2) strengthening visual identity via banners and stickers at production sites; and (3) registering business locations on Google Maps, including categories, photos, and business hours. The evaluation stage assessed listing visibility on Google Search/Maps, navigation ease, and early signals of increased visits. The report & dissemination stage documented good practices and shared them with nearby MSMEs. Initial outcomes indicate improved visibility (listings and product keywords are easier to find), better accessibility(visitors can navigate directly to sites), and growing potential for visits and transactions compared with conventional promotion. Economic gains are suggested by rising interest in starting similar businesses and broader reach beyond Bintoro. Key limitations include the three-month duration (constraining longitudinal updates), geographic coverage limited to Bintoro’s administrative area, low digital literacy among some participants (≈40% require continued assistance), and Google’s automated verification delays for several locations. Follow-up 3–6 months of mentoring plus tracking performance metrics (impressions, clicks, inquiries, orders, revenue) are recommended to ensure measurable and sustainable impact.